Immediate Free Jejunum Transfer for Salvage Surgery of Gastric Tube Necrosis - Hiroki Umezawa; Takeshi Matsutani; Rei Ogawa; Hiko Hyakusoku (Case Reports in Gastrointestinal Medicine)
Gastric tube necrosis after esophagus cancer surgery is a rare but critical situation. Salvage reconstruction of the esophagus remains a challenging procedure for head and neck surgeons. Historically, surgeons have employed a two-stage salvage surgery consisting of debridement followed by reconstruction. While this procedure generates good results, the time to restart oral alimentation is long. The present report describes the case of a 62-year-old male who developed gastric tube necrosis 3 days after undergoing surgery for thoracic-cervical esophageal cancer and immediate reconstruction with the retrosternal gastric pullup technique. He was treated with debridement and simultaneous free jejunum transfer 4 days after the primary surgery. He was able to restart oral alimentation 10 days after the salvage surgery. This rapid return to oral alimentation is a major advantage of the one-stage immediate esophagus salvage reconstruction. Another advantage is the ease of the reconstructive procedure: the absence of scarring and prolonged inflammation, which are disadvantages of the two-stage procedure, meant that recipient vessel selection and anastomosis were uncomplicated. The one-step procedure may be particularly useful in cases where the inflammation is discovered early.